FOSTERING STUDENT’S SPEAKING ABILITY BY USING TIKTOK APPLICATION - Manik, Putri Fadillah; Daulay, Sholihatul Hamidah; Siregar, Deasy Yunita (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research aimed to find out the TikTok application in fostering students' ability to speak in terms of fluency and accuracy. This research was conducted with a pre-experimental method. The sample of the research, respondents are students in grade 8 in Kelurahan Sari Rejo 2023/2024 which consisted of 15 students. The data were gathered through quantitative. When collecting data, the researcher gave a speaking test, the speaking test was divided into two steps, namely pre-test and post-test, while the researcher used the (t) test to analyze the data. The findings of this research show that the average score on the pre-test in terms of pronunciation is (5) and the post-test is (5.93). The average score for pre-test fluency is (2) and post-test is (5.06). And the total result of pronunciation and fluency or X1 is (3.5) and the post-test or X2 is (4.03). So it shows that students have improved in speaking after being taught via the TikTok application, and their English speaking skills are better.